Pengaruh Edukasi Stunting Terhadap Pengetahuan Dan Sikap Ibu Bayi Dalam Pencegahan Stunting Di Posyandu Kaca Piring - Yeti Trisnawati (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2022)
Background: Stunting is a dangerous nutritional problem today because it affects thefuture of children to adulthood. In Tanjungpinang City, the prevalence of stunting inTanjungpinang in 2018 was very high, at 25.28%. Parents, especially mothers, have avery important role in fulfilling children's nutrition. The mother's low knowledge and attitude towards stunting prevention can have an effect on increasing the incidence ofstunting in toddlers. For this reason, various health efforts need to be carried out to reducethe incidence. The purpose of this study was to determine the effect of stunting educationon mother's knowledge and attitudes in preventing stunting at the Kaca Piring Posyanduin the Working Area of the Malay Health Center in Piring City, Tanjungpinang City.Method: The research method used a quasi experimental one group pretest-posttestdesign. The population is mothers who have babies aged less than 1 year. Samples weretaken by 18 respondents by accidental sampling. The provision of education with theaudiovisual method is approximately 1 hour. Assessment of pretest and posttest with aquestionnaire instrument. Test the analysis using paired t-test.Result: The results showed that the mean difference between the pretest and postteston the knowledge variable was 4.17 with a p value of 0.001, while the attitude variableshowed that the mean difference between the pretest and posttest was 8.78, with a pvalue of 0.001. This shows that there are significant differences in knowledge andattitudes before and after stunting education. It was concluded that stunting educationwas effective in increasing the knowledge and attitudes of mothers with toddlers instunting prevention. Efforts are needed to provide continuous understanding so thatmothers better understand the problem of stunting and its prevention, especially inproviding nutritious food.Keywords: education, stunting, baby's mother